The Effects of Living Environment, Health Status of Family Members, and Migrant Elderly following Children's Attitude about Care on Grandchildren's Health Status in Weifang, China - Mingli Pang; Jieru Wang; Xiaoxu Jiang; Hexian Li; Shixue Li; Fanlei Kong (MDPI AG, 2022)
As urbanization is growing quickly in China, many migrant elderly following children (MEFC) migrate to big cities to care for their grandchildren (grandchildren of MEFC=GMEFC). This study aimed to explore the effects of the living environment, health statuses of family members, and MEFC's attitude regarding the care of their children (children of MEFC=CMEFC) for their GMEFC on GMEFC's health statuses in Weifang, China. Multistage cluster random sampling was used to select the participants, and 613 MEFC were included in total. Descriptive analysis, univariate analysis and binary logistic regression were used to investigate the association between the related variables and GMEFC's health statuses. It was found that 74.9% of the GMEFC had excellent health statuses. The GMEFC who had siblings, the CMEFC with excellent health statuses, and the MEFC with excellent health statuses were more likely to have excellent health statuses. Moreover, the GMEFC who were female, elevators occasionally malfunctioned, the MEFC who were dissatisfied with the CMEFC's time spent on caring, and the MEFC who did not understand or forgive the CMEFC's limited time on caring were less likely to have GMEFC with excellent health statuses. The results indicated that a better living environment, better health statuses of family members, and a positive attitude of the MEFC regarding the care of CMEFC for GMEFC would result in a better health status of GMEFC.